2021
DOI: 10.1097/nrl.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Stroke and Myocardial Infarction After Mild COVID-19 Infection

Abstract: Introduction: The concurrency of both, acute stroke and acute myocardial infarction in normal conditions, outside the pandemic is rare. Coagulopathy has been associated with the inflammatory phase of coronavirus disease (COVID-19) and might be involved in this concurrency. Cases Report: We describe 2 patients with previous mild or no symptoms of COVID-19, admitted for acute stroke with recent/simultaneous myocardial infarction in whom admission polymerase chain reaction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Furthermore, left atrial area evaluated with DESCT but not with TTE was related to mortality, as it was the evidence of major cardiovascular DESCT findings. In parallel, though very rare, during the COVID-19 pandemic a number or reports of concurrent AIS and MI have been published, which might underscore the potential usefulness of our findings in certain clinical scenarios [23].…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, left atrial area evaluated with DESCT but not with TTE was related to mortality, as it was the evidence of major cardiovascular DESCT findings. In parallel, though very rare, during the COVID-19 pandemic a number or reports of concurrent AIS and MI have been published, which might underscore the potential usefulness of our findings in certain clinical scenarios [23].…”
Section: Discussionmentioning
confidence: 62%
“…Chakir et al 18 reported a case of coincident myocardial infarction, bilateral pulmonary embolism and ischemic stroke without any identifiable etiologic factor, except COVID-19. Ruiz-Ares et al 19 described two cases with mild symptoms of COVID-19 admitted for acute stroke with recent/simultaneous myocardial infarction. All these case reports described thromboembolic events occurring during the acute phase of COVID-19, characterized by the hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem analysis of a series of patients with COVID-19 infection revealed evidence of endotheliitis and inflammatory cell infiltration across the vascular bed in various organs, including the heart [ 9 ]. A few case reports have shown that patients with resolved COVID-19 continue to be susceptible to thromboembolic complications, such as myocardial infarction and stroke during both immediate [ 5 ] and subacute post-infectious periods [ 4 ]. A 64-year-old woman with previous mildly symptomatic COVID-19 infection suffered an acute ischemic stroke and silent myocardial infarction five weeks after COVID-19 infection, albeit inflammatory markers were not elevated [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex interplay between endothelial dysfunction from direct viral infection and systemic inflammation is associated with various thrombotic complications and vasculitides [1,2]. Despite the resolution of the primary infection, vascular complications, including stroke, ST-elevation myocardial infarction (STEMI), and vasculitides, in various sites have been reported in a subset of patients [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%